COMPLIANCE OF MICRO SMALL MEDIUM ENTERPRISE TAX PAYERS TO GROSS REGIONAL DOMESTIC PRODUCT - Nawangsasi, Yuli; Nasrudin, Inayati; Purnamawati, Hilda (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
Increasing the number of Micro Small and Medium Enterprise local government of Bandung is a potential source of income from the local tax sector to increase development an economic city of Bandung. This research is to describe the role of tax payer compliance rate on Micro Small and Medium Enterprise to increase the Gross Regional Domestic Product as measured by the increase government expenditures of finance development of Bandung city during period 2013 – 2016. The method of study is descriptive verificatif by using the analytical tool Two Stage Least Square. The result of the analysis indicates that compliance of micro enterprise tax payers will impact to increase the gross regional domestic product through the increased government expenditures sourced from local tax revenues.